2013
DOI: 10.3390/molecules18055051
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids from the Herb of Leonurus japonicus

Abstract: Two new sesquiterpenoids, (−)-(1S*,2S*,3R*)-3-ethoxycupar-5-ene-1,2-diol (1) and (−)-(1S*,4S*,9S*)-1,9-epoxybisabola-2,10-diene-4-ol (2), along with six known compounds 3−8, were isolated from the EtOH extract of the herb of Leonurus japonicus. Their structures were elucidated by physical and spectroscopic analysis. In the in vitro assays, compounds 7 and 8 showed obvious antibacterial activity against several bacteria strains, while compound 3 significantly inhibited abnormal increase of platelet aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…This compound has demonstrated a large spectrum antibacterial and antifungal effect, as well as antioxidant and anti-inflammatory activity. Beta-caryophyllene also contributes to the antimicrobial properties of S. aromaticum with a broad effect on Gram positive bacteria, as reported by Xiong et al (2013). Regarding the main components of P. nigrum, most terpenes do not possess high inherent antimicrobial activity against many Gram-negative pathogens (Bagamboula et al, 2004;Nazzaro et al, 2013).…”
Section: Antibacterial Activity Of the Essential Oil Testedmentioning
confidence: 81%
“…This compound has demonstrated a large spectrum antibacterial and antifungal effect, as well as antioxidant and anti-inflammatory activity. Beta-caryophyllene also contributes to the antimicrobial properties of S. aromaticum with a broad effect on Gram positive bacteria, as reported by Xiong et al (2013). Regarding the main components of P. nigrum, most terpenes do not possess high inherent antimicrobial activity against many Gram-negative pathogens (Bagamboula et al, 2004;Nazzaro et al, 2013).…”
Section: Antibacterial Activity Of the Essential Oil Testedmentioning
confidence: 81%
“…60 Compound 3 ((2S,5S)-2-hydroxy-2,6,10,10-tetramethyl-1oxaspiro[4.5]dec-6-en-8-one), at a concentration of 10 μM, inhibited platelet aggregation induced by ADP. 61 As such, motherwort shows potential as an antiplatelet herbal medicine and clinical trials are suggested to test this potential action.…”
Section: Motherwort (Leonurus Japonicus)mentioning
confidence: 99%
“…has been used as traditional Chinese herbal medicine for thousands of years. The diverse therapeutic applications of L. japonicus may be attributed to its bioactive constituents, which include terpenoid, [ 1–3 ] alkaloids, [ 4 ] flavonoids, [ 4,5 ] glycosides, [ 6 ] peptides [ 7 ] and volatile oils. [ 8 ] Diterpenoids have become widely studied in recent years.…”
Section: Introductionmentioning
confidence: 99%